Future Changes in Tropical Cyclone and Easterly Wave Characteristics over Tropical North America - Christian Dominguez; James M. Done; Cindy L. Bruyère (Oceans, 2021)
Tropical Cyclones (TCs) and Easterly Waves (EWs) are the most important phenomena in Tropical North America. Thus, examining their future changes is crucial for adaptation and mitigation strategies. The Community Earth System Model drove a three-member regional model multi-physics ensemble under the Representative Concentration Pathways 8.5 emission scenario for creating four future scenarios (2020–2030, 2030–2040, 2050–2060, 2080–2090). These future climate runs were analyzed to determine changes in EW and TC features: rainfall, track density, contribution to seasonal rainfall, and tropical cyclogenesis. Our study reveals that a mean increase of at least 40% in the mean annual TC precipitation is projected over northern Mexico and southwestern USA. Slight positive changes in EW track density are projected southwards 10° N over the North Atlantic Ocean for the 2050–2060 and 2080–2090 periods. Over the Eastern Pacific Ocean, a mean increment in the EW activity is projected westwards across the future decades. Furthermore, a mean reduction by up to 60% of EW rainfall, mainly over the Caribbean region, Gulf of Mexico, and central-southern Mexico, is projected for the future decades. Tropical cyclogenesis over both basins slightly changes in future scenarios (not significant). We concluded that these variations could have significant impacts on regional precipitation.